Efficacy of direct-acting antivirals in patients with hepatitis C virus-associated cryoglobulinemic vasculitis: Results of a long-term follow-up - S. V. Gavrisheva; D. T. Abdurakhmanov; N. M. Bulanov; E. L. Tanashhuk; T. P. Rozina; E. N. Nikulkina; S. Yu. Milovanova; E. A. Nabatchikova; A. L. Filatova; E. E. Starostina; T. N. Krasnova; S. V. Moiseev (Научно-практическая ревматология)
Objective – to evaluate the long-term outcomes of HCV eradication with direct-acting antivirals (DAAs) in patients with hepatitis C-associated cryoglobulinemic vasculitis (HCV-CV)Materials and methods. We retrospectively assessed 48 patients with HCV-CV treated with DAAs. The activity of HCV-CV was assessed by using Birmingham Vasculitis Activity Score version 3 (BVAS v. 3). In patients with HCV-CV the rate of sustained virologic (defined as undetectable HCV-RNA levels 12 weeks after treatment cessation) and immunological (defined as absence of circulating cryoglobulins, rheumatoid factor and normal C4 level) response; and the rate of complete (defined by a BVAS v. 3 score of 0) and partial (defined as BVAS v. 3 score <50% of the baseline score) clinical response were evaluated. Immunosupressants were given before or after DAAs therapy if clinically needed.Results. Median time of follow-up from treatment cessation were 26,5 (11,5–62,3) months. All 48 (100%) patients achieved sustained virologic response. Elimination of cryoglobulins were reported in 20 (41,7%) patients, complete immunological response-in 4 (8,3%) cases. Complete and partial clinical responses were observed in 13 (27,1%) and 19 (39,6%) patients, respectively. BVAS v. 3 score <4 at baseline was independently associated with complete clinical response (ОR=7,58; 95% CI: 1,42–40,48; р=0,018). 3 (6,3%) patients demonstrated HCV-CV relapse.Conclusion. Patients with HCV-CV require a long-term follow-up period even after reaching the SVR. The use of BVAS v. 3 score before the DAAs therapy can facilitate the planning of therapeutic approach, particularly, when identifying the patients in whom the immunosupressive therapy should be considered after viral eradication.